Faktor Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Universitas Negeri Padang Berkarier di Lembaga Keuangan Syariah - Lathifah Rahmi Rafiqa; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2020)
The purpose of this study is to explore the impact of Shari'ah calculations, implications and knowledge on professional interests in Shariah financial institutions. The sample in this study is 88 students at Padang State University. The data used is distributed to primary data respondents in the form of queries. The pseudo-analysis method used in this article is the analysis of multiple linear regression.The results of the study show that ideas do not affect the interests of the profession in the financial institutions, and the motivations of sharia accounting and the influence of interest in any profession in the non-Shariah financial institutions.